2022
DOI: 10.30587/jcaa.v1i2.4832
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Good Corporate Governance Terhadap Kinerja Karyawan Pada PT. PLN (Persero) UP3 Baubau

Abstract: Tujuan utama penelitian ini adalah untuk mengetahui pengaruh Good Corporate Governance (Transparansi, Akuntabilitas, Tanggungjawab, Kesetaraan dan Kewajaran Terhadap Kinerja Karyawan.  Metode penelitian yang digunakan adalah deskriptif pendekatan kualitatif dan metode kuantitatif. Sampel penelitian adalah 47 Responden terdiri dari Karyawan PT.PLN (Persero) UP3 Baubau. Metode pengumpulan data menggunakan studi pustaka, Survey lapangan dan Kuisioner serta skala pengukuran menggunakan skala likert. Hasil peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…Therefore, they always perform their best quality of work, improving their performance. This result supports the study of Yuspitasari et al (2018) and Laode and Ridzal (2022), who found that fairness positively influenced employee performance.…”
Section: Nugraheni and Nasirohsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, they always perform their best quality of work, improving their performance. This result supports the study of Yuspitasari et al (2018) and Laode and Ridzal (2022), who found that fairness positively influenced employee performance.…”
Section: Nugraheni and Nasirohsupporting
confidence: 91%
“…Yuspitasari et al (2018) found that fairness positively influenced the employee performance of Islamic banks. A similar result was exposed by Laode and Ridzal (2022), that fairness and employee performance positively influenced the stateowned company. Hence, this study derived the hypothesis: H 5 : Fairness has a positive influence on employee performance.…”
Section: The Influence Of Fairness On Employee Performancesupporting
confidence: 69%
See 2 more Smart Citations